Pengaruh harga di tingkat petani ter Hadap keputusan petani menghasilkan Kopi bermutu tinggi (kasus di desaSukorejo kecamatan Tirtoyudo Kabupaten Malang =The Influence of Farmgate Price on Farmer's Decision toProduce Hig - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
The aim of this research is to estimate the relationship between quality and coffee bean prices at farm level, and to analyse its influence on farmer's decision to produce a different quality coffee beans. Cross-section primary selected using stratified-sampling method based on farmer's land-size holding.The quality of coffee beans was simply represented mechanical and hulling method conducted by farmers, namely, was used to analyse the effect of different quality of model was fitted to the data using Maximum Likelihood procedure in estimating factors affecting farmer's decision. The result showed that the price of better quality of coffee per kg was 42 rupiahs higher the lower one This implies that hedonic price established on market was able to affect farmer's decision to produce a higher quality of coffee beans by hulling mechanically. This research suggests that in encouraging farmers to produce a better quality of coffee is not necessary conducted by implementing standardization and grading system at farm level.